Family Functioning And Child Well-Being Amongst Urban Malay Single Mother Families Influence Of Risk And Protective Factors. - K. Doshi, Anjli Panalal (2005)
A large and growing number of Malaysian families with children are headed by single mothers. Past research has found that single mother families and their children experience more difficulties in the context of family life and well-being than two parent families. This study was designed to determine the contribution of risk and protective factors in predicting urban Malay single mothers' family functioning and child well-being. In addition, this study examined the moderating role of protective factors (risk x protective factor interaction) on the relationships between risk factors and family functioning and child well-being. Multiple factors in several domains (individual, family and extra familial) were identified as risk and protective factors. The risk factors were economic strain, depression, work stress and neighborhood problems. While, the protective factors were self-esteem, coping competence, parenting behavior and social support. Family functioning was composed of two subdimensions; cohesion and adaptability while child well-being consisted of three subdimensions, self-regulation, cognitive competence and self-worth. Findings from this study are based on the data collected from 158 urban Malay single mothers who had at least one child between the ages of six to twelve years. The most critical finding was the evidence to support the moderating role of protective factors on the relationships between risk factors and family functioning and child well-being. Overall, the risk and protective factors considered in this study explained between 17-35% of the variance in single mother's family functioning outcomes and 13-21% of the variance in child well-being outcomes. The findings imply that economic strain is the single most important risk factor affecting child well-being. Protective factors account for substantial variance in family functioning; they account for more unique variance (28%) than the risk factor measures (3%). There was evidence that the presence of protective factors was likely to reduce the impact of risk factors. Parenting behavior provided the best protective barrier between risk factors and family functioning. Findings also suggest that urban Malay single mothers with higher levels of protective factors are more likely to have better family functioning and child-well-being outcomes. In addition, results indicate that urban Malay single mother families that have balanced family functioning are more likely to have children with higher levels of child-well-being. The risk factor index (RFI) was found to be significantly related with all the child well-being outcomes but none of the family functioning outcomes. However, the protective factor index (PFI) was significantly related with both the outcomes. These results highlight the role of protective factors in promoting better family hnctioning and child well-being and the extent to which protective factors buffer risk factors that might compromise outcomes. Consideration should be given to both risk and protective factors in the design of interventions aimed at strengthening family functioning and enhancing child well-being in urban Malay single mother families.